Age-specific rise of income and consumption inequality - Guozhong Zhu (Kiel Institute for the World Economy (IfW), 2013)
Based on Panel Study of Income Dynamics (PSID) and Consumer Expenditure Survey (CEX), the author presents evidence that the rise of income/consumption inequality over the past decades is more significant among younger households. This is consistent with the theory that the secular rise of inequality is due to increasing heterogeneity in earning ability. The author further shows that such age-specificity implies significant changes to the previously documented life-cycle profiles of inequality which are the basis of many important economic inferences.
Keywords: C81; E21; J31; 330; age-specific inequality; consumption inequality; income inequality; life-cycle profile